A dielectric model for frozen mineral soils at a frequency of 435 MHz. Issue 9 (2nd September 2021) - Fomin, Sergey; Muzalevskiy, Konstantin
ABSTRACT: A single frequency refractive mixing dielectric model at 435 MHz for frozen mineral soils is proposed. The model was created based on the laboratory dielectric measurements of three soil samples in the ranges of soil moisture from 0.01cm 3 cm −3 to 0.42cm 3 cm −3, temperature from– 30°C to– 1°C, clay content (by weight) from 9.1% to 41.3%. Coefficient of determination R 2 and root mean square error (RMSE) predicted by the model and measured values for real () and imaginary () part of the complex relative permittivity (CRP) are = 0.988 (= 0.323) and = 0.987 (= 0.100). Compared to well-known spectroscopic models, this model is simpler in practical engineering use. The input parameters of the model are the volumetric soil moisture, temperature and the content of the clay fraction. The output parameters are the real and imaginary parts of the CRP. The created model may be used to develop new remote sensing retrieval algorithms of temperature, the content of unfrozen water and ice in the root zone of frozen soils for northern regions. ε   ′ ε   ′ ′ R ε   ′ 2 R M S E ε   ′ R ε   ′ ′ 2 R M S E ε   ′ ′